ERRORS AS A RESOURCE IN FOREIGN LANGUAGE LEARNING FOR ADULTS IN THE SYSTEM OF CONTINUING EDUCATION - Khraban , Tetiana (Continuing Professional Education: Theory and Practice, 2025)
The purpose of this study is twofold: firstly, to thoroughly examine the role of errors in adult foreign language learning within the context of continuing education, and secondly, to identify and substantiate effective pedagogical methods and strategies that aim to cultivate a positive perception of errors and enhance the efficacy of learning. The present study was conducted in the form of a systematic literature review, which allows for an in-depth analysis of relevant scientific works with the aim of summarizing contemporary approaches to studying the phenomenon of learning from errors in teaching foreign languages to adult learners in the context of continuing education. The corpus of the study comprised scientific publications that offered theoretical justifications, practical recommendations, and empirical findings concerning the utilization of errors as a learning resource in the pedagogy of foreign language teaching for adults. A systematic review clearly demonstrates that errors in the pedagogy of foreign language teaching for adult learners in continuing education are not merely unavoidable, but may also contribute to the efficacy of the learning process. Errors serve a dual purpose in the educational process. They function as diagnostic tools to identify problems in a student’s understanding of a subject. Additionally, errors can serve as a catalyst for the development of critical thinking skills, metacognition, and independent learning. The provision of a pedagogically safe environment is a prerequisite for the role of errors in the cultivation of critical thinking, confidence, and an active attitude toward learning. The existence of a “positive error climate”, characterized by an accommodating and supportive teaching approach toward errors, is identified as a pivotal element in facilitating effective error management. A critical component of effective teaching strategies is their adaptation to the level of training, motivational attitudes, and emotional state of learners. The efficacy of feedback, whether explicit or implicit, is contingent upon its ability to accommodate individual needs and learning styles. The review further emphasizes the critical role of emotions in the processing of errors. Emotions such as anxiety, shame, pride, or curiosity have the capacity to both enhance learning motivation and impede cognitive activity. Consequently, the integration of elements of emotional competence and the formation of self-regulation strategies is particularly salient for adult audiences. The implementation of effective techniques aimed at enhancing error awareness encompasses a variety of approaches, including but not limited to the maintenance of linguistic diaries, collaborative efforts, comparison with established standards, self-diagnosis, and the provision of feedback. These strategies are designed to address language deficiencies while fostering a more profound comprehension of linguistic structures.